Chemical Mechanical Planarization of Carbon-Doped Amorphous Ge2Sb2Te5 Film with Hydrogen Peroxide as Oxidizer in Alkaline Slurry. (21st January 2020) - Feng, Daohuan; Liu, Weili; Liu, Yuxiang; Song, Zhitang; Wang, Weilei; Wei, Zhen; Zhao, Gaoyang
Abstract : In this study, we investigate the chemical mechanical planarization (CMP), static dissolution and electrochemical performace of amorphous carbon-doped Ge2 Sb2 Te5 (GSTC) film in alkaline slurry with H2 O2 employed as an oxidizer. It was found that the material removal rate (MRR) of GSTC first increase and then slowly decrease with the increase in concentration of H2 O2 . The surface quality of the GSTC post-CMP shows the same trend. To understand the mechanism of GSTC CMP with H2 O2, the Energy Dispersive Spectrometer on the surface of the GSTC post-CMP, Inductively Coupled Plasma of the solution after static dissolution, potentiodynamic polarization curve and X-ray photoelectron spectroscope are measured and it is found that the change in carbon state is an important factor for the CMP of GSTC. Finally, a possible removal mechanism of GSTC in different concentrations of H2 O2 in the alkaline slurry is proposed.